Genetic Risk Factors, Biology, Psychosocial Aspects, and Comparison between Male Breast Cancer and Female Breast Cancer (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: men at higher risk to reduce symptom duration before diagnosis